Transplanted gene-modified placental cells boost FVIII activity in pediatric sheep without eliciting immunity, toxicity, or adverse events - Trevisan, Brady; Rodriguez, Martin; Ramamurthy, Ritu; George, Sunil; Babatunde, Oluwaseun O.; Dizon, Jacqueline; Shields, Jordan; Lankford, Shannon; Schwahn, Denise; Gautreaux, Michael; Farland, Andrew; Owen, John; et al. (Frontiers in Immunology, 2026)
BackgroundThe current standard of care for Hemophilia A (HA), a hereditary bleeding disorder caused by mutations in the Factor VIII (F8) gene, include FVIII replacement proteins, engineered clotting factors, and a broad array of new therapeutics including antibodies and gene therapy. These therapies allow persons with HA (PHA) to have near normal life expectancies, but the burden of disease continues to be high, with 30% of PHA developing FVIII inhibitors, considerably increasing the risk of morbidity and mortality.ObjectiveThe present study tested the ability of human placental cells (PLC), transduced with a lentivector encoding a codon-optimized, bioengineered FVIII transgene (mcoET3) (PLC-mcoET3) to increase FVIII activity levels after administration to pediatric large animals. In addition, we determined whether administration of PLC-mcoET3 would induce inhibitor formation, and defined how the immune response to infused human FVIII (hFVIII) or ET3 proteins differed from that of administration of PLC-mcoET3.MethodsPediatric sheep at 8–12 months of age were used in this study. PLC-mcoET3 providing 20 IU/kg of ET3/infusion/sheep were administered intravenously (IV) or intraperitoneally (IP), and control groups received the same dose/kg of purified recombinant ET3 or human full-length recombinant FVIII protein (hFVIII). Plasma FVIII activity, presence of anti-FVIII/ET3 humoral or cellular immune responses, and immunologic responses using a multiplexed gene expression panel were assessed.Results and conclusionData show that while intravenous (IV) infusion of ET3 or hFVIII to pediatric sheep results in a high level of inhibitory antibodies, administration of PLC-mcoET3 IV is safe, and resulted in increased plasma FVIII activity for at least 15 weeks without the formation of anti-ET3/FVIII inhibitory antibodies.